Scrub Typhus in Children at Tribhuvan University Teaching Hospital in Nepal - Bajracharya L (Dove Medical Press, 2020)
Luna Bajracharya Department of Pediatrics, Maharajgunj Medical Campus, Tribhuvan University Teaching Hospital, Kathmandu, NepalCorrespondence: Luna Bajracharya Email lunabajracharyalb@gmail.comIntroduction: Scrub typhus is an acute undifferentiated febrile illness with varied nonspecific manifestations. It dramatically responds to appropriate antibiotic if started earlier in the course of disease leading to significant reduction in morbidities and mortalities.Objective: To describe the clinical profile, treatment and prognosis of scrub typhus in children.Patients and Methods: Serologically confirmed children with scrub typhus admitted to Tribhuvan University Teaching Hospital (TUTH) over a period of 3 years (April 15, 2015, to April 14, 2018) were retrospectively analyzed for clinical manifestations, investigations, complications and treatment outcomes.Findings: A total of 84 children (39 boys, 45 girls) were found to have serologically confirmed scrub typhus. Apart from fever which was invariably present in all children, the most common symptoms were that of respiratory system such as shortness of breath, gastrointestinal system which were vomiting and abdomen pain followed by headache. On physical examination, the most frequent clinical signs were hepatosplenomegaly, edema, eschar and lymphadenopathy. Hepatitis, myocarditis and meningitis were the most common complications. Most patients had the shortest defervescence of less than 48 hours with oral doxycycline (64.7%) followed by intravenous chloramphenicol (56.7%). The overall mortality rate was 4.8%, all due to multiorgan dysfunction.Conclusion: In a country like Nepal, scrub typhus should be suspected in any child who presents with fever associated with shortness of breath, abdomen pain, vomiting, headache and clinical findings suggestive of multisystem involvement such as hepatitis, myocarditis or meningitis. Early empirical medical management based on high clinical suspicion while waiting for definitive serological report with oral doxycycline or intravenous chloramphenicol may prevent complications of scrub typhus thereby reducing mortality.Keywords: children, chloramphenicol, doxycycline, fever, Nepal, scrub typhus